Una poetica della riduzione e del residuo: l’apocalisse in El obsceno pájaro de la noche di José Donoso (Altre Modernità, 2013)
The hypothesis to be verified in this work is that José Donoso proposes and constructs in El obsceno pájaro de la noche, by means of an accurate use of narrative strategies, an apocalyptic vision of the individual world, as represented by the narrator Mudito, as well as of the social and political context of Chile in the 60s, represented by the more general conflict between power and marginalization. This vision takes its proper center in the spatial dimensions of the characters, by means of two topoi: the house and the body. The progressive disintegration of bodies and places takes control of the narrative and weakens it to the point of excluding any trace of persistence. In the continuous movement between antithesis and connection to the Revelation of St. John the Divine, a poetics of the residual is developed that puts into crisis the power of the word and the power of narration.
Keywords: Letteratura cilena; José Donoso; El obsceno pájaro de la noche; apocalisse